Diversity and selection of wild food plants in six regions of Northwestern Iberian Peninsula (Spain and Portugal) - Pardo de Santayana, Manuel (2008)
This paper compares the traditional knowledge and use of wild edible plants in six rural regions of the Northwest of the Iberian Peninsula. Five of them are in Spain: Campoo, Picos de Europa, Piloña, Sanabria and Caurel and the sixth is in Portugal, Parque Natural de Montesinho.